ECG leads I and II to evaluate diuresis of patients with congestive heart failure admitted to the hospital via the Emergency Department - Suthaporn Lumlertgul (2018)
Background: Attenuation of electrocardiogram (ECG) QRS complexes is observed in patients with a variety of illnesses and peripheral edema (PERED), and augmentation with alleviation of PERED. Serial ECGs in stable individuals display variation in the amplitude of QRS complexes in leads V1-V6, stemming from careless placement of recording electrodes on the chestwall. Electrocardiographs record only leads I and II, and mathematically derive the other four limb leads in real time. This study evaluated the sum of the amplitudes of ECG leads I and II, along with other sets of ECG leads in the monitoring of diuresis in patients with congestive heart failure (CHF). Methods: Twenty patients with CHF had ECGs and weights recorded on admission and at discharge. The amplitude of the QRS complexes in all ECG leads were measured and sums of I and II, all limb leads, V1-V6, and all 12 leads were calculated. Results: There was a good correlation between the weight loss and the increase in the sums of the amplitudes of the QRS complexes from leads I and II (r = 0.55, P = 0.012), and the six limb leads (r = 0.68, P = 0.001), but a poor correlation with the V1-V6 leads (r = 0.04, P = 0.85) and all 12 leads (r = 0.1, P = 0.40). Conclusions: Sums of the amplitudes of the ECG QRS complexes from leads I and II constitute a reliable, easily obtainable, ubiquitously available, bedside clinical index, which can be employed in the diagnosis, monitoring of management, and follow-up of patients with CHF. © 2009, The Authors.